FORMULATION AND EVALUATION OF NEUSILIN US2 ADSORBED AMORPHOUS SOLID SELF-MICROEMULSIFYING DELIVERY SYSTEM OF ATORVASTATIN CALCIUM ® - Khade, Shweta; Pore, Yogesh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of the present study was to improve the dissolution profile of poorly water-soluble atorvastatin calcium (ASC), via formation of its solid self-microemulsifying drug delivery system (SSMEDDS). Methods: The SSMEDDS was prepared using oleic acid, Tween 80 and propylene glycol as an oil phase, surfactant, and co-surfactant, respectively. Initially, the solubility of ASC was examined in different oils, surfactants and co-surfactants, and pseudo-ternary phase diagrams were constructed subsequently to optimize the ratio of the excipients having greater microemulsion region. The liquid self-emulsifying batches of ASC were developed with the optimized excipients and evaluated for droplet size, zeta potential, percentage transmittance, self-emulsification time assessment, dispersibility test, and drug release. Neusilin US2 was employed as an adsorbent to transform optimized liquid emulsifying batch A1 to solid formulation. The solid formulation was characterized by particle size analysis, differential scanning calorimetry, X-ray powder diffractometry, scanning electron microscopy, and in vitro drug release. ® Results: The characterization studies revealed the transformation of crystalline ASC to amorphous form in solid adsorbed batch. The drug release studies demonstrated remarkable improvement in dissolution profile of ASC from its liquid as well as SSMEDDS as compared to pure drug. Conclusion: The development of SSMEDDS could be a reliable and alternative approach for improvement of dissolution performance of ASC. Keywords: Atorvastatin, Self-microemulsifying, Amorphous, Formulation, Neusilin ® US2.